Comprehensive Analysis to Identify the Encoded Gens of Sodium Channels as a Prognostic Biomarker in Hepatocellular Carcinoma - Yan, Yan; He, Wen; Chen, Yonghua; Li, Qiang; Pan, Jiahao; Yuan, Yunfei; Zeng, Weian; Chen, Dongtai; Xing, Wei (Frontiers in Genetics, 2022)
The SCN family as the encoded gens of sodium channels has been proven to participate in development of cancers including hepatocellular carcinoma (HCC), but the prognostic value of the SCN family is unclear. The results of the UALCAN database had showed that SCN2A/4A/5A/8A mRNA were highly expressed in tumour tissues, while SCN1A/7A/11A mRNA were expressed at low levels (P < 0.05), furthermore, the expression of SCN4A and SCN7A had the similar levels in microarray analysis result. The pan-tumour analysis showed that SCN7A expression was stably lower in tumours than SCN4A expression by TIMER. Both SCN4A and SCN7A were related to tumour grade, nodal metastatic status, histological subtype, patient race, individual cancer stages and TP53 mutation status to varying degrees. The Kaplan–Meier plotter demonstrated that high SCN4A mRNA expression was correlated with better overall survival (OS), disease-specific survival (DSS) and progression-free survival (PFS) and that high expression of SCN7A mRNA was associated with better OS; however, in Asians, higher SCN4A was correlated with better OS and DSS, and higher SCN7A was well correlated with better OS, recurrence-free survival (RFS), DSS and PFS. Analysis of data from cBioPortal showed that mutation of SCN7A was related to RFS and PFS. The protein expression of SCN4A and SCN7A had been detected by Immunohistochemistry. Univariate survival analysis revealed that high SCN7A protein expression was significantly linked to better OS (P = 0.001) and RFS (P = 0.003). Moreover, SCN7A displayed as an independent prognostic factor by multivariate analysis. In addition, a lower methylation level indicated a poor outcome. Pathway and functional enrichment analysis predicted a relationship between SCN7A and the PI3K pathway. In conclusion, there are significant and stable changes in SCN4A and SCN7A expression in HCC. SCN7A expression has better prognostic value and might participate in HCC progression.